1941
DOI: 10.1001/archpedi.1941.02000080035005
|View full text |Cite
|
Sign up to set email alerts
|

Lead Poisoning

Abstract: Examination of the records of patients with lead poisoning admitted to the Children's Hospital of Philadelphia revealed a seasonal incidence in the onset of encephalopathic symptoms. Figure 1 shows the monthly distribution of onset of symptoms of the patients with frank lead encephalopathy admitted to this hospital.In constructing this figure only patients with frank encephalopathic symptoms of rather acute onset were counted; patients with latent or subclinical plumbism, usually discovered accidentally, who e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1942
1942
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other effects of light in lead poisoning have been noted. Acutely poisoned rabbits excreted even greater amounts of coproporphyrin following exposure to ultraviolet light ( 12), perhaps related is the higher incidence of clinical lead poisoning appearing in the summer months ( 13). Other diseases of porphyrin metabolism, porphyria cutanea tarda and South African porphyria, are characterized by lightinduced skin symptoms with normal red cell porphyrins.…”
mentioning
confidence: 99%
“…Other effects of light in lead poisoning have been noted. Acutely poisoned rabbits excreted even greater amounts of coproporphyrin following exposure to ultraviolet light ( 12), perhaps related is the higher incidence of clinical lead poisoning appearing in the summer months ( 13). Other diseases of porphyrin metabolism, porphyria cutanea tarda and South African porphyria, are characterized by lightinduced skin symptoms with normal red cell porphyrins.…”
mentioning
confidence: 99%
“…A number of workers including Rapoport and Rubin (1941) have shown that in the great majority of cases symptoms appear during the late spring and summer months. This has been attributed to sunlight causing increased absorption of metal from the bowel, the intake and mobilization of lead being intimately related to calcium metabolism, while experimental work has shown that vitamin D has no effect on poisoning by inhalation.…”
Section: Clinical Findingsmentioning
confidence: 99%